Pengaruh Tingkat Pendidikan, Kecerdasan Emosional Dan Komitmen Kerja Terhadap Kinerja Pegawai Kantor Camat Kotarih - Syafrizal, Rodi (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
The aim of this research is to determine the influence of education level, emotional intelligence and work commitment on the performance of Kotarih sub-district office employees. The population in this study were all employees of the Kotarih sub-district office, totaling 35 respondents. The data source in this research comes from primary data, namely from the results of collecting questionnaires filled in directly by respondents. Hypothesis testing uses multiple regression analysis on the SPSS version 25 application. The results of this study show that partially the level of education and work commitment have no effect on employee performance, while emotional intelligence has a significant effect on the performance of Kotarih sub-district office employees. Simultaneously or together, the level of education, emotional intelligence and work commitment have a significant effect on the performance of Kotarih sub-district office employees